Walruses recovering after 60+ years of protection in Svalbard, Norway - Kit M. Kovacs (Polar Research, 2014)
Walruses were brought to the brink of extinction in Svalbard (Norway) during 350 years of unregulated harvesting. They became protected in 1952, when few remained. During the first 30 years of protection, approximately 100 animals became established within the archipelago, most of which likely came from Franz Josef Land, to the east. A marked recovery has taken place since then. This study reports the results of a photographic aerial survey flown in summer 2012, covering all current and historical haul-out sites for walruses in Svalbard. It provides updates regarding the increasing numbers of: (1) land-based haul-out sites (from 78 in 2006 to 91 in 2012); (2) occupied sites (from 17 in 2006 to 24 in the 2012 survey); (3) sites with mother–calf pairs (which increased from a single site with a single small calf in 2006 to 10 sites with a total of 57 small calves in 2012) and; (4) a 48% increase in abundance in the six-year period between the two surveys to 3886 (confidence interval 3553–4262) animals, including animals in the water at the time of the survey. Future environmental change might reduce benthic production in the Arctic, reducing the prey-base for walruses, and also impact walruses directly via declines in their sea-ice breeding habitat. But, currently the Svalbard walrus population is growing at a rate that matches the theoretical maximum rate of growth that has been calculated for recovering walrus populations under favourable environmental conditions with no food limitations.